Crataegus marshallii, Parsley Hawthorn - Michael G. Andreu; Melissa H. Friedman; Mary McKenzie; Heather V. Quintana; Robert J. Northrop (EDIS)
FOR 255, a 2-page fact sheet by Michael G. Andreu, Melissa H. Friedman, Mary McKenzie, Heather V. Quintana, and Robert Northrop, describes this small native tree found in open to partially shaded areas along the moist edges or slopes of floodplains, river banks, and wet woodlands throughout the southeastern United States — scientific and common names, description, allergen, and applications. Includes references. Published by the UF School of Forest Resources and Conservation, June 2010.